Protesi di rivestimento di anca - Calanna, F.; Gala, L. (Lo Scalpello - Journal, 2019)
HIP RESURFACING ARTHROPLASTYHip resurfacing arthroplasty is a concept of hip replacement surgery developed specifically for young and activepatients. Femoral bone stock preservation and restoring of normal anatomy of the hip joint allow for betterfunctioning, with increased frequency and duration of sporting activities. Patient-related factors leading to worseoutcomes have also been identified. Moreover, concerns about metal-on-metal bearings with adverse reaction to metaldebris have led to a recent drop-off in this kind of procedure. The purpose of this study was to evaluate current trendsabout hip resurfacing and comparing it to standard hip replacement arthroplasty. Hip resurfacing still represents aviable option with a correct indication, in the right hands and using a device with a long track record.